The impact of acculturation and interpersonal communication on the Adaptation of East African University Students in Malaysia - Wanda, Judith Flora; Tan, Huey Pyng (Penerbit Universiti Kebangsaan Malaysia, 2023)
The objective of the study was to explore how acculturation and interpersonal communication impacts the adaptation of East African students in Malaysia. Research samples were selected strictly based on the original formation of East Africa (Kenya, Uganda and Tanzania), university students in Malaysia. Just like other international students these students face challenges to adapt in a new culture while striving to achieve their academic goals. To test the study’s hypotheses, a statistical package for service solution (SPSS) 20.0 was used to analyse data collected from 240 respondents. This study's theoretical framework was derived from Gu's (2008) Acculturation Scale for Asian International Students (ASAIS) and Rubin and Martin’s (1994) Interpersonal Communication Competence Scale (ICCS). These two studies were used independently to examine and identify any effects that acculturation may have on interpersonal communication. According to Pearson's correlation test, acculturation and interpersonal communication are all significantly negatively correlated. However, the results of the study indicated a significant difference in the length of stay and interpersonal communication for the adaptation of East African university students in Malaysia for the Independent t-test. In other words, the longer an international student stays in a country to pursue his or her goal, the better their interpersonal communication skills get. The results of this study show that both acculturation and interpersonal communication impacts the adaptation of these international students at different levels. This study looks forward to stimulating future studies of other international students’ acculturation processes from communication perception. Communication researchers can play a vital role in promoting understanding between and among ethnic communities and the host societies.